Impact of Age and Hearing Impairment on Work Performance during Long Working Hours - Wagner-Hartl, Verena (Int J Environ Res Public Health, 2018)
Based on demographic prognoses, it must be assumed that a greater number of older workers will be found in the future labor market. How to deal with their possible age-related impairments of sensory functions, like hearing impairment and work performance during extended working time, has not been addressed explicitly until now. The study addresses this interplay. The study was performed on two consecutive days after normal working hours. The 55 participants had to “work” in the study at least three additional hours to simulate a situation of long working hours. The tested measures for (job) performance were: general attention, long-term selective attention, concentration, and reaction time. All of the investigated variables were taken at both days of the study (2 × 2 × 2 repeated measurement design). The results show effects for age, the interaction of hearing impairment and time of measurement, and effects of the measurement time. Older participants reacted slower than younger participants did. Furthermore, younger participants reacted more frequently in a correct way. Hearing impairment seems to have a negative impact especially on measures of false reactions, and therefore especially on measurement time 1. The results can be interpreted in a way that hearing-impaired participants are able to compensate their deficits over time.